(untitled) (Journal of the College of Basic Education, 2022)
The puppet theater is one of the forms of the student’s theater and its fields: it is a performing art in its own right, which has its origins, rules and methods of expression, as it relies on operating or moving the blood or cracks and passes-through in an artistic way for the purpose of entertainment, education and education. The blood theater has several terms, labels and concepts that are synonymous or almost synonymous with them The Blood Theater and the Mar Unit Theater, the Karakiz Theater, the Araguz Theater, the Karrah Theater Goz and the Qarqosh Theater ... It is called the Puppet Theater or the Mar Unit, because it depends on its operation and activation on the blood and puppets, as the current research aims to identify the employment of the Puppet Theater in the development of students in Grade A Tuck in the primary art education. As the current research required due to its nature and what it aims at adopting the experimental research approach, this approach is characterized by its high accuracy and is considered one of the closest approaches in research to solve theoretical and applied educational problems because it sets an acceptable limit of control for the exotic variables that can affect the dependent variable. As the number of primary schools in the third Rusafa Directorate reached (303), the number of students in the primary stage (201163) reached one male and one female pupil (104068) male and (97095) females, and the researcher obtained the numbers from the Statistics and Planning Division of the Ministry of Education, and she was unable The researcher is able to obtain only the number of first graders in the third Rusafa District due to lack of availability.